(untitled) (Eurasian Medical Research Periodical, 2022)
There are many different causes of spine illnesses, including degeneration, trauma, congenital problems, and other particular variables. Throughout their lifetimes, the majority of people may encounter a range of spine illness symptoms that may occasionally be treated with non-invasive or invasive procedures. For the proper management of spine disease, it is crucial to accurately diagnose the pathology of the spine. Several imaging modalities, including radiography, computed tomography (CT), magnetic resonance imaging (MRI), and other studies like EOS, bone scans, single photon emission CT/CT, and electrophysiologic tests, can be used for the diagnosis. The decision of the diagnostic modality must be patient (or case) specific, thus we should be familiar with their fundamental characteristics and methods. We go into great depth regarding the many diagnostic techniques (such as radiography, CT, MRI, electrophysiologic study, and others) that are frequently used to diagnose spine diseases..